Proyecto de “elaboración y comercialización de productos a base de chocolate - Veliz, J. (2010)
Our project is based on the implementation of a Chocolate’s Shop, whose main raw material is the Ecuadorian chocolate, thus taking advantage of the region’s fertility we conducted a market study which one revealed optimal results and that motivated us to develop it. Taking in consideration that there is no direct competition, since there’s not exist a Chocolate’s shop in Guayaquil city, we concluded that the business is feasible and also has an increasing projection so that it would be a very interesting investment to any capitalist. In our variety of exquisite products, you could find: chocolate candies, cakes, pies, truffles, and personalized chocolates for special occasions, among many other original delicacies, of which most are creations that comes from exclusive recipes of our Chocolate’s Chef, what makes us unique in the city and probably in the country. Therefore, this is a strategic advantage in the market for us. The highlight of our project is that the investment recovery is fast and it is not necessary a working